Magnitude and factors associated with postoperative depression among adult orthopedics patients during COVID-19 pandemics: A multi-center cross-sectional study - Seid Tegegne, Shimelis; Fentie Alle, Yewlsew (Frontiers in Psychiatry, 2022)
Background: Postoperative depression is one of the devastating problems and important health concerns in adult orthopedics surgical patients. It is often under-diagnosed and appropriate perioperative management of patients is recommended. This study aimed to determine the magnitude and factors associated with postoperative depression among orthopedics patients in Ethiopia. Materials and Method: This multi-center cross-sectional study was conducted on 443 adult post-orthopedics surgical patients. All the data were entered and analyzed with SPSS version 25. Bivariable and multivariable logistic regression was used to identify the associated factors with the outcome variable. P-values <0.05 were taken as statistically significant with 95 % CI. Data were collected after distributing 9-item standard patient health questionnaires and the Oslo-3 item social support scale tool. Result: Based on our study result, the magnitude of postoperative depression among adult orthopedics surgical patients was 61.8 % (95 % CI: 56.8- 65.7). Using multivariable logistic regression analysis, factors which had an association with postoperative depression were female in gender, Farmer in occupation, having a history of previous substance use, history of anxiety, Patients who had moderate to poor social support, BMI less than 18.5 kg/m2, and patients who had an open fracture. Conclusion: The magnitude of postoperative depression was high. Due emphasis needs to be given to screening and treatment of postoperative depression, especially among patients of the female gender, farmer occupation, moderate to poor social support, history of substance use and anxiety, low BMI, and open fracture.